2012
DOI: 10.1242/jcs.110296
|View full text |Cite|
|
Sign up to set email alerts
|

ZNRF2 is released from membranes by growth factors and, together with ZNRF1, regulates the Na+/K+ATPase

Abstract: SummaryHere, we describe a phosphorylation-based reverse myristoyl switch for mammalian ZNRF2, and show that this E3 ubiquitin ligase and its sister protein ZNRF1 regulate the Na + /K + pump (Na + /K + ATPase). N-myristoylation localizes ZNRF1 and ZNRF2 to intracellular membranes and enhances their activity. However, when ZNRF2 is phosphorylated in response to agonists including insulin and growth factors, it binds to 14-3-3 and is released into the cytosol. On membranes, ZNRF1 and ZNRF2 interact with the Na +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 43 publications
2
26
0
Order By: Relevance
“…For example, the E3 ligase Itch protein alters its catalytic activity through a conformational change by c-Jun amino-terminal kinase-mediated phosphorylation, which induces the disruption of an intramolecular inhibitory interaction ( Gallagher et al, 2006 ). The phosphorylation of ZNRF2, another member of the ZNRF protein family, influences its interaction with the substrate, the 14–3-3 protein, and its association with intracellular membranes ( Hoxhaj et al, 2012 ). In this context, the phosphorylation of ZNRF2 at serine 19, which is located outside the zinc finger region responsible for substrate binding, releases ZNRF2 from the plasma membrane to the cytosol, resulting in decreased catalytic activity.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the E3 ligase Itch protein alters its catalytic activity through a conformational change by c-Jun amino-terminal kinase-mediated phosphorylation, which induces the disruption of an intramolecular inhibitory interaction ( Gallagher et al, 2006 ). The phosphorylation of ZNRF2, another member of the ZNRF protein family, influences its interaction with the substrate, the 14–3-3 protein, and its association with intracellular membranes ( Hoxhaj et al, 2012 ). In this context, the phosphorylation of ZNRF2 at serine 19, which is located outside the zinc finger region responsible for substrate binding, releases ZNRF2 from the plasma membrane to the cytosol, resulting in decreased catalytic activity.…”
Section: Discussionmentioning
confidence: 99%
“…ZNRF1 encodes an E3 ubiquitin-protein ligase that plays a role in neuralcell differentiation. It has been reported to interact with tubulin, promote Wallerian degeneration and regulate Na + /K + ATPase [25][26][27]. COLEC12 encodes a member of the C-lectin family.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study showed that the E3 ubiquitin ligase ZNRF2 is an enzyme tethered to intracellular membranes, via an N-myristoyl moiety, where it ubiquitylates the Na + /K + ATPase pump ( Hoxhaj et al, 2012 ). ZNRF2 is robustly phosphorylated on Ser19, Ser82 and Ser145 in response to growth factors, phorbol ester (PMA) and forskolin.…”
Section: Introductionmentioning
confidence: 99%